Global analysis of a plant-hare dynamic with stage structures. Issue 4 (1st January 2012) - Gu, Xiang; Xia, Yonghui
A plant-hare model with stage structure for plant is proposed in this paper. By analysing the corresponding characteristic equations, the local stability of the equilibria is investigated and Hopf bifurcations occurring at the positive equilibrium under some conditions are demonstrated. Taking time delay τ as bifurcating parameter, the direction and stability of Hopf bifurcation are carried out.